The Electrospray (ESI) and Flowing Atmosphere-Pressure Afterglow (FAPA) Mass Spectrometry Studies of Nitrophenols (Plant Growth Stimulants) Removed Using Strong Base-Functionalized Materials - Mateusz Pawlaczyk (MDPI AG, 2021)
The functional silica-based materials functionalized with a strong nitrogen base TBD (SiO2-TBD) deposited via a linker or with a basic poly(amidoamine) dendrimer containing multiple terminal amine groups -NH2 (SiO2-EDA) and functional polymers containing a strong phosphazene base (Polymer-Phosphazene) or another basic poly(amidoamine) dendrimer (PMVEAMA-PAMAM) were tested as sorbents dedicated to a mixture of nitrophenols (p-nitrophenol and 2-methoxy-5-nitrophenol), which are analogs of nitrophenols used in plant growth biostimulants. The adsorptive potential of the studied materials reached 0.102, 0.089, 0.140, and 0.074 g of the nitrophenols g−1, for SiO2-TBD, SiO2-EDA, polymer-phosphazene, and PMVEAMA-PAMAM, respectively. The sorptive efficiency of the analytes, i.e., their adsorption on the functional materials, the desorption from the obtained [(sorbent)H+ − nitrophenolates–] complexes, and interactions with the used soil, were monitored using mass spectrometry (MS) technique with electrospray (ESI) and flowing atmosphere-pressure afterglow (FAPA) ionizations, for the analysis of the aqueous solutions and the solids, respectively. The results showed that the adsorption/desorption progress is determined by the structures of the terminal basic domains anchored to the materials, which are connected with the strength of the proton exchange between the sorbents and nitrophenols. Moreover, the conducted comprehensive MS analyses, performed for both solid and aqueous samples, gave a broad insight into the interactions of the biostimulants and the presented functional materials.